2004
DOI: 10.1021/bm049685b
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Motions in Chitosan Studied by Dielectric Relaxation Spectroscopy

Abstract: Neutralized and nonneutralized chitosan films subject to different thermal treatments were studied by dielectric relaxation spectroscopy from -130 to +150 degrees C in the frequency range between 20 Hz and 1 MHz. Two main relaxation processes, both arrhenian type, were detected: process I at temperatures below 0 degrees C with a mean activation energy of 49 +/- 1 kJ mol(-1), which has the characteristics of a secondary relaxation process related with local chain dynamics, and process II observable at higher te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
52
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 20 publications
10
52
1
2
Order By: Relevance
“…7 Due to water losses of the sample by evaporation, the conductivity is reduced in the following runs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…7 Due to water losses of the sample by evaporation, the conductivity is reduced in the following runs.…”
Section: Resultsmentioning
confidence: 99%
“…7 The dielectric measurements were carried out using a Hewlett-Packard impedance analyzer HP 4284A, covering a frequency range from 20 Hz to 1 MHz, under an applied electric field of 1 V rms . The temperature control was assured by the Quatro Cryosystem from Novocontrol GmbH (Hundsangen, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…By using dielectric spectroscopy, Viciosa et al 29 reported two relaxation processes with an Arrhenius temperature dependence for wet (13% of water content) and annealed (for 20 min at 150 C) non-neutralized and neutralized forms of Cs. The first process (located at temperature between À100 C and 0 C) has the characteristic of a secondary relaxation process which was related to local chain dynamics, and the second process located at higher temperatures which were related to conductivity.…”
Section: Introductionmentioning
confidence: 99%